Multiple Oral Leiomyomas in an Infant: A Rare Case - Efraín Alvarez; María P. Laberry; Carlos M. Ardila (Case Reports in Dentistry)
Oral leiomyoma is a benign smooth muscle tumor that occurs most frequently in the uterine myometrium, gastrointestinal tract, and skin. Incidence in the oral cavity is considered uncommon. Most cases are reported in adults, with very few cases described in children. A rare case of multiple leiomyomas localized on the tongue, cheek, and floor of the mouth of an 8-month-old baby is reported. The diagnosis of leiomyoma in the oral cavity is mainly determined by histological studies; however, immunohistochemical tests are recommended in order to differentiate from other tumors. Surgical excision of the lesion appears to be the best treatment option. A review of the literature did not reveal any previously reported case of multiple oral leiomyomas.